1D Photonic Topological Insulators Composed of Split Ring Resonators: A Mini Review - Guo, Zhiwei; Wang, Yuqian; Ke, Shaolin; Su, Xiaoqiang; Ren, Jie; Chen, Hong (Advanced Physics Research, 2024)
In recent years, topological photonics inspired by electric topological insulators has promoted extensive research on robust electromagnetic (EM) wave manipulation and new wave‐functional devices. Optical resonators can significantly confine EM waves and are the basic building blocks for constructing diverse topological structures under a tight binding mechanism. As an artificial “magnetic atom,” the split‐ring‐resonator (SRR) is one of the most attractive optical resonators. SRRs provide an excellent and flexible platform for constructing various topological structures with complex coupling distributions, uncovering abundant topological properties, and innovating practical devices. Here, the realization and fundamental EM responses of the SRR are briefly introduced. Compared to conventional EM resonance elements, the coupling between SRRs depends not only on the coupling distance but also on the orientation angle of the slits. The recent achievements in various low‐dimensional photonic topological structures composed of SRRs are summarized. Furthermore, this review explains the underlying physical principles and discusses progress in topological devices with SRRs, including wireless power transfer, sensing, and switching. Finally, this review provides an overview of the future of SRR topological structures and their impact on the development of novel topological systems and devices. Compared to the disks or spheres, the coupling coefficients between split‐ring‐resonators are not only dependent on the separating distance, but also related to the relative rotation angle. Topological chains with split‐ring‐resonators provide a good platform to study complex topological models, and reveal important applications.